A Social‐Ecological Systems Approach to Enhance Sustainable Farming and Forestry in the EU. (3rd September 2018) - Dwyer, Janet; Berriet‐Solliec, Marielle; Lataste, François Gaël; Short, Chris; Maréchal, Anne; Hart, Kaley
Summary: The two concepts of public goods and ecosystem services are often used to describe the same welfare benefits potentially generated by agriculture and forestry, but they originate from different perspectives and each offer only partial analysis of these relationships. A more holistic approach – Social‐Ecological Systems (SES) – has been adapted and applied in new research to understand more fully how the relationships can best be characterised, and beneficial change promoted, through policy reforms and practical action. An important and novel part of the description of a SES, as developed under the PEGASUS project, is the assessment of its 'valorisation cascade'. Through the mapping and consideration of assets, actors, interactions, drivers and the nature of the valorisation cascade in 34 diverse case studies, the project highlighted the importance of multi‐actor approaches and social processes to foster beneficial change. These include collective action, co‐learning and trust between actors, promoting experimentation and innovation, developing public and/or consumer awareness and identifying new valorisation options, including via commercial supply chains and enhanced community involvement. Abstract : The two concepts of public goods and ecosystem services are often used to describe the same welfare benefits potentially generated by agriculture and forestry, but they originate from different perspectives and each offer only partial analysis of these relationships. A more holistic approach – Social‐Ecological Systems (SES) – has been adapted and applied in new research to understand more fully how the relationships can best be characterised, and beneficial change promoted, through policy reforms and practical action. An important and novel part of the description of a SES, as developed under the PEGASUS project, is the assessment of its 'valorisation cascade'. Through the mapping and consideration of assets, actors, interactions, drivers and the nature of the valorisation cascade in 34 diverse case studies, the project highlighted the importance of multi‐actor approaches and social processes to foster beneficial change.